(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to examine the indications, demographic features and histopathological diagnosis category of renal biopsies evaluated at the Pathology Laboratory of the University of Health Sciences Diyarbakır Gazi Yasargil Training and Research Hospital. Materials and Methods: The information of 190 patients who underwent percutaneous renal needle biopsy between July 2017 and February 2020 was obtained from the approved final pathology reports. Results: 190 biopsies were performed. 60% (n=114) and 40% (n=76) of the biopsies were native and transplant, respectively. 59.5% of the patients were male. Four of the patients were under 18 years. The mean ages of the native and transplant biopsy groupes were 37±14, and 34±14, respectively. Proteinuria was the most common biopsy indication (79.5%).Nonspecific changes were the most common diagnosis of the native biopsies. It was followed by focal segmental glomerulonephritis (FSGS), membranous glomerulonephritis (MGN), and IgA nephritis (IgAN). The most common secondary cause of glomerulonephritis was lupus nephritis. Acute cellular rejection was the most common diagnosis of the transplant renal biopsies. Conclusion: Proteinuria was identified as the most common indication for biopsy. In the present study, the primary glomerular disease was FSGS while the secondary was lupus nephritis. With electron microscopic examination, it might be possible to decrease the number of patients who cannot be definitively diagnosed histomorphologically.